Robust Association Between Changes in Coronary Flow Capacity Following Percutaneous Coronary Intervention and Vessel-Oriented Outcomes and the Implication for Clinical Practice - Hamaya, Rikuta; Yonetsu, Taishi; Sayama, Kodai; Matsuda, Kazuki; Ueno, Hiroki; Nagamine, Tatsuhiro; Misawa, Toru; Hada, Masahiro; Hoshino, Masahiro; Sugiyama, Tomoyo; Sasano, Tetsuo; Kakuta, Tsunekazu (Frontiers in Cardiovascular Medicine, 2022)
Backgrounds: Coronary flow capacity (CFC) is a potentially useful physiologic marker of ischemia for guiding percutaneous coronary intervention (PCI) indication, while the changes through PCI have not been investigated. Objectives: To assess the determinants and prognostic implication of delta CFC, defined as the change in the CFC status following PCI. Methods: From a single center registry, 450 patients with chronic coronary syndrome (CCS) who underwent fractional flow reserve (FFR)-guided PCI with pre-/post-PCI invasive coronary physiological assessments were included. Associations between PCI-related changes in thermodilution method-derived CFC categories and incident target vessel failure (TVF) were assessed. Results: The mean (SD) age was 67.1 (10.0) years and there were 75 (16.7%) women. Compared with patients showing no change in CFC categories after PCI, patients with category worsened, +1, +2, and +3 category improved had the hazard ratio (95% CI) for incident TVF of 2.27 (0.95, 5.43), 0.85 (0.33, 2.22), 0.45 (0.12, 1.63), and 0.14 (0.016, 1.30), respectively (P for linear trends = 0.0051). After adjustment for confounders, one additional improvement in CFC status was associated with 0.61 (0.45, 0.83) times the hazard of TVF. CFC changes were largely predicted by the pre-PCI CFC status. Conclusion: CFC improvement following PCI, which was largely determined by the pre-PCI CFC status, was associated with lower risk of incident TVF in patients with CCS who underwent PCI. CFC changes provide a mechanistic explanation on a potential favorable effect of PCI on reducing vessel-oriented outcome in lesions with reduced CFC and low FFR.